The legal system for working time: analysis of the legal framework and the role of collective bargaining - Aguas-Blasco, Ana; Lafuente-Pastor, Vicente Pedro; Callau-Dalmau, María Pilar; Rico-Letosa, Sara; De Val-Arnal, José Jesús; Aguilar-Martín, María Carmen; Alcázar-Ortiz, Sara; Álvarez-Gimeno, Rafael; Pedrosa-Alquézar, Sonia Isabel; Vallejo-Dacosta, Ruth María; Torrente-Gari, Susana; González-Labrada, Manuel; et al. (Acciones e Investigaciones Sociales, 2023)
Working time, as a legal institution, takes a central position in Employment and Labor Law. This has been so since its origins and throughout its development, but now it presents new perspectives and challenges in its regulation, being the legal frame of reference insufficient in its contents, which demands the unavoidable intervention of collective bargaining to complete it.This paper analyzes the legal framework of working time and allow to discover all those potentialities of collective bargaining as a regulatory source of this working condition, in all its aspects.In particular, important aspects are studied such as: working day, work breaks, working hours, overtime, work permits, work vacations, digital switch-off. It also offers an analysis of working time from the perspective of the reconciliation of personal and family life with work, as well as from the perspective of feminism.Finally, we identify the new spaces open to negotiation between workers' representatives and the employer and proposals are presented.
Keywords: Working time; working day; work break; digital switch-off; collective bargaining